Baseline and interim PET‐based outcome prediction in peripheral T‐cell lymphoma: A subgroup analysis of the PETAL trial. Issue 3 (18th February 2020) - Schmitz, Christine; Rekowski, Jan; Müller, Stefan P.; Hertenstein, Bernd; Franzius, Christiane; Ganser, Arnold; Bengel, Frank M.; Kroschinsky, Frank; Kotzerke, Jörg; La Rosée, Paul; Freesmeyer, Martin; Hoeffkes, Heinz‐Gert; et al.
Abstract: The prospective randomized Positron Emission Tomography (PET)‐Guided Therapy of Aggressive Non‐Hodgkin Lymphomas (PETAL) trial was designed to test the ability of interim PET (iPET) to direct therapy. As reported previously, outcome remained unaffected by iPET‐based treatment changes. In this subgroup analysis, we studied the prognostic value of baseline total metabolic tumor volume (TMTV) and iPET response in 76 patients with T‐cell lymphoma. TMTV was measured using the 41% maximum standardized uptake value (SUV41max ) and SUV4 thresholding methods. Interim PET was performed after two treatment cycles and evaluated using the ΔSUVmax approach and the Deauville scale. Because of significant differences in outcome, patients with anaplastic lymphoma kinase (ALK)‐positive lymphoma were analyzed separately from patients with ALK‐negative lymphoma. In the latter, TMTV was statistically significantly correlated with progression‐free survival, with thresholds best dichotomizing the population, of 232 cm 3 using SUV41max and 460 cm 3 using SUV4 . For iPET response, the respective thresholds were 46.9% SUVmax reduction and Deauville score 1‐4 vs 5. The proportion of poor prognosis patients was 46% and 29% for TMTV by SUV41max and SUV4, and 29% and 25% for iPET response by ΔSUVmax and Deauville, respectively. At diagnosis, the hazard ratio (95% confidence interval) for poor prognosis vs good prognosis patients according to TMTV was 2.291 (1.135‐4.624) for SUV41max and 3.206 (1.524‐6.743) for SUV4 . At iPET, it was 3.910 (1.891‐8.087) for ΔSUVmax and 4.371 (2.079‐9.187) for Deauville. On multivariable analysis, only TMTV and iPET response independently predicted survival. Patients with high baseline TMTV and poor iPET response (22% of the population) invariably progressed or died within the first year (hazard ratio, 9.031 [3.651‐22.336]). Due to small numbers and events, PET did not predict survival in ALK‐positive lymphoma. Baseline TMTV and iPET response are promising tools to select patients with ALK‐negative T‐cell lymphoma for early allogeneic transplantation or innovative therapies.